The National Science and Technology Fair Project in Costa Rica: A Journey through Its History, Contributions, Challenges, and Possibilities - Cambronero, Jeudy Alonso (2025)
The ED-112 National Science and Technology Fair has been pioneering work since the 1980s, promoting scientific and technological culture and vocations in Costa Rican society. Its work includes developing teacher training processes, executing the National Fair event, and collaborating with the Ministry of Innovation, Science, Technology and Telecommunications, the Ministry of Public Education, and the State Universities within the framework of the National Science and Technology Fairs Program Commission. Despite its achievements, the project also faces multiple challenges, such seeking sustainable financing, strengthening links with actors related to science and technology education, participation in international fairs, as well as expanding the scope of training processes. However, it should be noted that, in recent years, opportunities have arisen to advance and renew the project. These include greater involvement of the member institutions of the National Science and Technology Fairs Program in the national fair event, as well as the implementation of recreational-academic activities in science that enrich the experience of both teachers and students during the national fair event. This paper provides a historical review of the work of the ED-112 National Science and Technology Fair, describing the path it has taken from its beginnings to the present. It also discusses the project's objectives and its lines of work. Finally, it reflects on its contributions to Costa Rican education, the challenges and opportunities for the future, from its inception to the present.